Dampak Pengembangan Kawasan Industri Bolok Terhadap Subordinasi Perempuan Di Kupang, Nusa Tenggara Timur - Didimus Dedi Dhosa; Paulus AKL Ratumakin (ISJN Journal, 2021)
The development of the Bolok Industrial Zone in Kupang of East Nusa Tenggara Province has resulted in not only land acquisition, exclusion of farmers and ecological destruction but also in woman subordination. This research was conducted in the village of Kuanheum in Kupang regency, East Nusa Tenggara Province from April through November 2019. It found that the expansion of capitalism necessitated the appropriation of land in the Bolok Industrial Zone which on the one hand gave advantages to the capital owner and the state bureaucracy but on the other hand caused disadvantages to women around the area as they were constructed as the second class. The results of the social construction can be outlined as follows. First, women do not have right of ownership over communal land upon which they can do their business. Secondly, the denial of land ownership for women has resulted in little participation of women in the deliberation on land cultivation and on the impact of land acquisition. Thirdly, women are differentiated in three distinct groups namely women of the landowners, female tenants and female newcomers. The class differentiation of women has brought about the fizzling out of woman movement to defend their land when they are confronted with male dominance, state hegemony and expansion of land appropriating corporations. Abstrak Pembangunan Kawasan Industri Bolok di Kupang, Nusa Tenggara Timur, bukan saja menyebabkan akuisisi tanah, eksklusi petani, dan destruksi ekologi melainkan juga menyebabkan subordinasi terhadap perempuan. Penelitian ini dilakukan di desa Kuanheum di Kupang pada April hingga November 2019. Tulisan ini menemukan bahwa ekspansi kapitalisme membutuhkan tanah di Kawasan Industri Bolok yang pada satu sisi menguntungkan pemilik kapital dan aparatur negara, akan tetapi pada sisi lain merugikan perempuan. Perempuan di Kawasan Industri Bolok dikonstruksi sebagai kelas dua. Konsekuensi dari konstruksi demikian adalah pertama, perempuan tidak memiliki hak atas tanah ulayat sebagai basis produksi. Kedua, ketiadaan hak atas tanah berdampak pada minimnya partisipasi perempuan dalam pertimbangan mendalam tentang pengelolaan tanah dan dampak akuisisi tanah. Ketiga, adanya diferensiasi kelas perempuan, yang dapat dibedakan atas tiga karakteristik yakni perempuan dari kalangan tuan tanah, perempuan penggarap, dan perempuan pendatang dari luar desa Kuanheum yang bekerja sebagai penggarap. Diferensiasi kelas perempuan telah menyebabkan melempemnya gerakan perempuan untuk mempertahankan tanah ketika berhadapan dengan dominasi laki-laki, hegemoni aparatur negara dan ekspansi korporasi yang mengakuisisi tanah.